Gender-based differences in the relationships among proactive personality, perceived entrepreneurial support and entrepreneurial intention of Chinese private college students: A moderated mediation model - Tian, Jing; Zhang, Mohan; Wu, Yunpeng; Zhou, Haitao (Frontiers in Psychology, 2022)
Proactive personality is a key determinant of entrepreneurial intention. Few studies have explored the mediating and moderating mechanisms underlying this relationship. This study investigates the association between proactive personality and entrepreneurial intention and examines the mediating role of perceived entrepreneurial support and the moderating role of gender. Using a cross-sectional design, 1,515 senior students (women = 838, men = 677) from Chinese private colleges were recruited using random cluster sampling. They completed a battery of self-reported online questionnaires on proactive personality, perceived entrepreneurial support, and entrepreneurial intention. The results revealed that perceived entrepreneurial support mediates the association between proactive personality and entrepreneurial intention. Moderated mediation analysis indicated that the relationship between proactive personality and perceived entrepreneurial support and that between perceived entrepreneurial support and entrepreneurial intention are moderated by gender. Specifically, the positive association between proactive personality and entrepreneurial intention was stronger in male students, and the positive association between perceived entrepreneurial support and entrepreneurial intention was stronger in female students. This study contributes to the understanding of how proactive personality predicts entrepreneurial intention in Chinese private college students and bears implications for higher education institutions and policymakers that entrepreneurship promotion agenda should focus on improving perceived entrepreneurial support and considering the gender of students.